Artisan air-dry clay : the beginner's guide to easy, inexpensive & stylish no-kiln pottery - Hostašová, Radka, 1997- (Stash Books, 2022)
No Kiln? No Problem! Learn to make beautifully textured home décor accents with inexpensive air-dry clay! The process is easy, and the results are surprisingly stylish when you follow the tips, advice, and instruction from author and clay artist-designer Radka Hostasova. Aimed at absolute beginners-this book starts with an overview of the tools and materials needed to produce the best results. A comprehensive "Getting Started" chapter teaches essential home pottery techniques such as rolling slab, coiling, sculpting, and pinching. Also included are creative ideas for adding color with acrylic paint, watercolor, and metallics. At the book's heart are a range of beautiful projects, including trinket bowls, napkin rings, wall hangings, coasters, and others. Each lesson comes with a detailed reference photograph and easy-to-follow step-by-step instructions.--